Twelve Steps to a Compassionate Life - Armstrong, Karen (Karachi Oxford University Press, 2011)
Shares practical recommendations for promoting world peace by cultivating one's intrinsic tendencies for compassion, outlining a program for achieving mindfulness and engaging in acts of kindness.
Include Index
Keywords: Compassion -- a